Terahertz Spin Current Dynamics in Antiferromagnetic Hematite - Hongsong Qiu; Tom S. Seifert; Lin Huang; Yongjian Zhou; Zdeněk Kašpar; Caihong Zhang; Jingbo Wu; Kebin Fan; Qi Zhang; Di Wu; Tobias Kampfrath; Cheng Song; et al. (Advanced Science, 2023)
Abstract An important vision of modern magnetic research is to use antiferromagnets (AFMs) as controllable and active ultrafast components in spintronic devices. Hematite (α‐Fe2O3) is a promising model material in this respect because its pronounced Dzyaloshinskii‐Moriya interaction leads to the coexistence of antiferromagnetism and weak ferromagnetism. Here, femtosecond laser pulses are used to drive terahertz (THz) spin currents from α‐Fe2O3 into an adjacent Pt layer. Two contributions to the generation of the spin current with distinctly different dynamics are found: the impulsive stimulated Raman scatting that relies on the AFM order and the ultrafast spin Seebeck effect that relies on the net magnetization. The total THz spin current dynamics can be manipulated by a medium‐strength magnetic field below 1 T. The control of the THz spin current achieved in α‐Fe2O3 opens the pathway toward tailoring the exact spin current dynamics from ultrafast AFM spin sources.